2020
DOI: 10.1016/j.cub.2020.02.054
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and Development at the Origin of a Phylum

Abstract: Highlights d Four echinoderm body plans were established in the Early Paleozoic d Body-plan distinctiveness was amplified by extinction and confounded by convergence d Disparity increased through the Cambrian and plateaued in the Ordovician d Higher-order features could be altered through time, enabling later innovation Authors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 73 publications
1
23
0
Order By: Relevance
“…The same authors criticizing our approach rely on analyses that do not provide detailed delineation of character state parameters, full probing of superficial similarity, or support for why a given transformation series should be a part of a given character or carry phylogenetic signal (Kammer et al, 2013;Sumrall, 2017;Wright, et al, 2017;Deline, et al 2020;inter alia).…”
Section: Character Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The same authors criticizing our approach rely on analyses that do not provide detailed delineation of character state parameters, full probing of superficial similarity, or support for why a given transformation series should be a part of a given character or carry phylogenetic signal (Kammer et al, 2013;Sumrall, 2017;Wright, et al, 2017;Deline, et al 2020;inter alia).…”
Section: Character Analysismentioning
confidence: 99%
“…The focus is primarily on feeding appendages but includes observations from adjacent skeletal anatomy as well. This analysis is based on examination of specimens hitherto unexamined by those who have suggested a sister-group relationship to crinoids for this taxon (Sheffield and Sumrall, 2019b; Deline et al, 2020). Accompanying reasoning that strongly supports a position for Eumorphocystis contrary to this recent work is presented with this analysis.…”
Section: Character Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…have never been examined under a comprehensive quantitative phylogenetic framework. Consequently, the main phylogenetic predictions of the EAT pertaining to the evolutionary relationships of Cambrian and Ordovician echinoderms, such as the origin of the crown group from edrioasteroid-like ancestors [14][15][16][17], although analysed with other homology schemes [9,11,18], have yet to be critically tested using EAT.…”
Section: Introductionmentioning
confidence: 99%
“…Echinoderms show complex patterns of morphological disparity and taxonomic diversity throughout their evolutionary history (Sumrall 1997; Deline 2015; Deline and Thomka 2017; Deline et al 2020) and have been suggested to respond to long-term environmental and climatic patterns (Paul 1968; Clausen 2004; Dickson 2004; Clausen and Smith 2005, 2008; Zamora and Smith 2008; Rahman and Zamora 2009). The early Paleozoic experienced large shifts in geochemical cycles (Haq and Schutter 2008; Trotter et al 2008; Rasmussen et al 2016; Albanesi et al 2019) that impacted microfossil and marine invertebrate groups (reviewed in Stigall et al 2019), suggesting that blastozoan echinoderms would have been impacted.…”
Section: Introductionmentioning
confidence: 99%